Lakossági jelzáloghitelezés termékfejlesztési kihívásai - Máté-Kasza Pál (2015)
The purpose of this thesis is to provide a thematic review of residential mortgage lending as one of the leading products in residential retail financing segment. Residential retail loans play an important role in residential financing as they can facilitate private residential property acquisition and impact other key participants in the residential property market. The primary purpose of this thesis is to provide a historical review and explore the current opportunities and challenges of the Hungarian residential retail lending market. An outlook at the international residential financing market highlights two key operational models: the two-tier lending model most prevalent in commonwealth countries and the single tier German model most common in continental Europe including Hungary. However, private debt brought on by residential lending also influences the economic viability of private individuals as well as other market participants. In addition, market development strategies pursued by financial institutions and regulatory changes also impact the quality of lending portfolios. The above has been well reflected in general residential lending practices in Hungary in the past 15 years. Until 2008 residential mortgage lending practices had been characterised by increasingly risk-taking but equally complex conditions that enabled a relatively easy access to home loans for a wide range of private individuals thanks to the less stringent financial market regulations in place at the time. Global recession; however, presented the Hungarian banking system with unprecedented challenges due to the structure of lending portfolios. In response, financial institutions turned toward more conservative lending policies and decreased their lending activity. The resulting systematic risk in turn incited regulatory bodies to enforce more stringent regulations and terms and conditions for residential home loans. Given an increasingly stringent regulatory environment, product development by institutional lenders has been hampered causing banks to focus on the development of lending processes. Besides these, significant resources are used in managing and restructuring of non-performing loan portfolios created before 2008.